Being is Creation. Why You Should Not Talk About Creation Only in the Context of Classically Understood Art? - Kłos-Czerwińska, Paulina (Sensus Historiae, 2021)
In my article I start with Peter Hallward’s assumptions concerning creation and I try to justify the title claim stating that one should not always talk about creation only in the context of classically understood art. Then, I put forward an even stronger thesis, which amounts to saying that it is our being rooted in everyday routine, our everyday choices and the accompanying emotions that deserve the name of the only true art. Thanks to this statement and its further analysis, I try to make it possible to imagine existence as creation and thus to provoke an essential change in the perception of art as such.